Neurological disease suspected to be caused by tick‐borne encephalitis virus infection in 6 horses in Switzerland. (12th September 2022) - Magouras, Ioannis; Schoster, Angelika; Fouché, Nathalie; Gerber, Vinzenz; Groschup, Martin H.; Ziegler, Ute; Fricker, Raffael; Griot, Christian; Vögtlin, Andrea
Abstract: Background: Reports on acute tick‐borne encephalitis virus (TBEV) infections with signs of neurologic disease in horses are limited. Objectives: To describe the epidemiological, clinical, and laboratory findings of suspected acute TBEV infections in 6 horses. Animals: Six horses originating from TBEV endemic regions of Switzerland were presented to equine hospitals with acute onset of neurologic disease between 2011 and 2019. Methods: Retrospective case series. Horses with acute onset of signs of neurologic disease that were subjected to clinical and microbiological examinations to rule out infectious diseases affecting the central nervous system. Results: All horses exhibited acute signs of neurologic disease including ataxia and proprioceptive deficits. Horses tested positive for TBEV using virus neutralization test and samples were further tested for TBEV‐specific IgM. The presence of TBEV‐specific IgM antibodies was confirmed in 5 horses (cases 1‐5, Laboratory Unit [LU] values ranging from 30 to 56). One horse (case no. 6) with an LU value just below the test threshold (LU = 22.3) was also included under the hypothesis that the horse was transitioning from acute to chronic infection. All horses originated from areas where humans with confirmed tick‐borne encephalitis reported to have been bitten by ticks. Conclusions and Clinical Importance: Acute TBEV infection should be a differential diagnosis in horses with signs of neurologic disease and originating from TBEV endemic areas. The establishment of harmonized diagnostic criteria would help to overcome the diagnostic challenges associated with TBEV and other Flavivirus infections in horses.